Comparison of anti-peritoneal fibrotic effects between an mTORC1-specific blocker and a PI3K/mTOR dual-blocker. (1st January 2019) - Xu, Tian; Lin, Tao; Xie, Jingyuan; Ren, Hong; Chen, Nan; Wang, Weiming
Abstract: Objective: To compare the anti-peritoneal fibrotic effects between a mammalian target of rapamycin complex 1-specific blocker and a phosphatidyl-inositol 3-kinase/mammalian target of rapamycin dual-blocker. Methods: A total of 40 male Sprague-Dawley rats were randomly divided into five groups with eight animals per group. The normal group (N group) did not receive any intervention. The normal saline group (NS group) received an intraperitoneal injection of normal saline at 1 ml/100 g daily. The model group (3 W group), rapamycin (RAPA) group and BEZ235 (PI3K/mTOR dual-blocker) group all received an intraperitoneal injection of 0.1% chlorhexidine gluconate at 1 ml/100g daily. And the RAPA and BEZ235 groups also received a 0.5 mg/d RAPA or 2.5 mg/d BEZ235 gavage every day, respectively. Rats in each group were sacrificed after 3 weeks. Results: Immunohistochemistry, real-time PCR and western blotting analysis of fibrosis-related indicators (FN, Col 1, and α-SMA) confirmed that RAPA and BEZ235 significantly inhibited peritoneal fibrosis and that these two drugs had similar effects. The p-Akt, p-mTOR, p-p70S6K expression levels were significantly up-regulated in the 3 W group compared to the NS group, confirming that the mTOR pathway was significantly activated during peritoneal fibrosis. RAPA significantly inhibited the phosphorylation of mTOR and p70S6K but did not have significant effects on p-Akt upstream of mTOR. BEZ235 had significant inhibitory effects on all signaling molecules (p-Akt, p-mTOR, and p-p70S6K) in the mTOR pathway. Conclusion: RAPA did not up-regulate p-Akt in a negative feedback fashion. Both drugs effectively inhibited peritoneal fibrosis.